Radiation Suffering and Patriotic Body Politics in the 1970s and 1980s. (7th April 2015) - Zaretsky, Natasha
Abstract: The human body was at the center of multiple protest movements after 1968. This essay considers one particular type of body that entered political space in the 1970s and 1980s: the cancer-afflicted bodies of those who had been exposed to radiation from the manufacture, testing, and detonation of atomic weapons in the late 1940s and 1950s. Beginning in the late 1970s, radiation sufferers and their relatives became politically mobilized: they created a national support network, testified to the pain unleashed by radiation-induced illness, and pursued avenues for gaining financial compensation for their suffering. This essay argues that these sufferers were crucial mediating figures who simultaneously incorporated elements from the anti-war movement of the 1960s and reflected the ascendancy of conservatism. They mobilized a "patriotic body politics" that linked physical illness to a growing conviction that the state had abandoned its most patriotic citizens. In the process, even as they drew on the left for inspiration, radiation sufferers advanced a vision that would prove enduring within the late twentieth century conservative imaginary: that of a deceptive government that had turned its back on the very citizens who had been most willing to incur sacrifices on its behalf. The essay thus uses the case of radiation activism to highlight the ways in which post-Vietnam conservatism incorporated elements from the very anti-war movement it ostensibly opposed, including its core insight that the state had the capacity to transform bodies into fodder.